The Implications of Setting in Zadie Smith's Wife of Willesden - Meerian, Allison (Kansas State University. Dept. of English., 2025)
After the borough of Brent won London Borough of Culture in 2020, celebrated contemporary English author, Zadie Smith, was selected to commemorate Brent through a work of literature. She chose to adapt a 14th century poem, The Wife of Bath, by the “Father of English Literature,” Geoffery Chaucer, into a play, The Wife of Willesden. Smith's masterful subversion of setting in her play reflects the current multiculturalism of Brent through an adaptation of the centuries old text. Placing The Wife of Willesden in pre-abolition Jamaica transforms the narrative, themes and subtext of Chaucer’s original. Through an exploration of Jamaican folklore and major historical events, such as the Windrush scandal, the adaptation proves to be a story created to celebrate and understand contemporary concepts of cultural identity, intersectionality, and immigration all through Smith’s masterful subversion of setting.
Kirmser Undergraduate Research Award - Continued Research category, honorable mention
Keywords: Zadie Smith; Literary Adaptation and Subversion; Geoffery Chaucer; The Wife of Willesden; Intersectionality and Immigration Themes